PENDAMPINGAN PRAKTIK PENGAMALAN IBADAH (PPI) KELAS VI UNTUK MENINGKATKAN KESADARAN SPIRITUAL SISWA MIN 2 KOTA PALANGKA RAYA - Ekayanti, Febriani; Istiyati Mahmudah (Universitas Nias Raya, 2024)
The Worship Practice Assistance Program (PPI) at MIN 2 Palangka Raya City aims to increase the spiritual awareness of grade VI students through guidance on daily worship practices. This program is motivated by the need to ensure that the religious knowledge taught at school can be applied by students in real life. Mentoring activities are carried out through theoretical guidance, direct worship practices at school and evaluation. The results of the mentoring showed a significant improvement in students' discipline in performing worship, a better understanding of worship procedures, and more positive character building. In addition, the active involvement of parents in accompanying students' worship at home plays an important role in maintaining the continuity of religious education between school and family. This program has also succeeded in increasing students' spiritual awareness, which is reflected in changes in behavior that are more polite, honest, and caring for the surrounding environment. Based on the results obtained, it is concluded that the PPI program is effective in guiding students to become more disciplined and understand the importance of worship and noble moral values. For the sustainability of the program, it is recommended that mentoring be carried out on an ongoing basis, actively involving parents, and utilizing technology to support students' worship practices at home.